Litho-facies and paleotectonic background of hydrocarbon reservoirs in North Kalinov gas-condensate field (Tomsk Oblast) - Ten, Tatyana Georgievna; Panova, Elena Vladimirovna; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
Based on micro-macroscopic core analysis, geophysical field data, contour mapping and referencing detailed litho-facies and paleotectonic investigation of Upper Jurassic pay thickness in North Kalinov gas condensate field was conducted. Paleotectonic analysis reflected the structure development history and determined the formation and distribution of oil fields.
Keywords: месторождения углеводородов; газоконденсатные месторождения; Томская область; палеотектонический анализ; нефтяные месторождения